2021
DOI: 10.3389/fmars.2021.652293
|View full text |Cite
|
Sign up to set email alerts
|

Stock Assessment of Small Yellow Croaker (Larimichthys polyactis) Off the Coast of China Using Per-Recruit Analysis Based on Bayesian Inference

Abstract: This paper presents a framework for quantifying uncertainty in per-recruit analysis for small yellow croaker (Larimichthys polyactis) fisheries in China, in which credible estimates of life history parameters from Bayesian inference were used to generate the distribution for a quantity of interest. Small yellow croakers were divided into five spatial groups. The status of each group was examined using a yield-per-recruit (YPR) model and a spawning stock biomass-per-recruit (SSBPR) model. The optimal length at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For instance, the stock status of L. polyactis was estimated to be in the green quadrant of its Kobe plot (neither overfished nor overfishing occurred) across all years except for the initial year. Previous assessments using Bayesian statespace surplus production models indicated that L. polyactis was overfished and overfishing occurred since the 1980s (Ma et al, 2020), the conclusion of overfishing was also supported by recent per-recruit analysis (Zhu et al, 2021). Apart from L. polyactis, three other stocks (S. japonicus, S. niphonius, and T. lepturus) were also previously assessed by surplus production models (Li et al, 2010;Zhang et al, 2015;Sui et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…For instance, the stock status of L. polyactis was estimated to be in the green quadrant of its Kobe plot (neither overfished nor overfishing occurred) across all years except for the initial year. Previous assessments using Bayesian statespace surplus production models indicated that L. polyactis was overfished and overfishing occurred since the 1980s (Ma et al, 2020), the conclusion of overfishing was also supported by recent per-recruit analysis (Zhu et al, 2021). Apart from L. polyactis, three other stocks (S. japonicus, S. niphonius, and T. lepturus) were also previously assessed by surplus production models (Li et al, 2010;Zhang et al, 2015;Sui et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…The first application of the data-limited approach to new species (e.g., Angelini et al, 2021;Falsone et al, 2021;Geraci et al, 2021;Shi et al, 2022;Tsikliras et al, 2021;Wang et al, 2021;Wang et al, 2022;Zhang et al, 2021;Zhang et al, 2022;Zhu et al, 2021).…”
mentioning
confidence: 99%